2010
DOI: 10.1038/npp.2010.226
|View full text |Cite
|
Sign up to set email alerts
|

Repeated N-Acetyl Cysteine Reduces Cocaine Seeking in Rodents and Craving in Cocaine-Dependent Humans

Abstract: Addiction is a chronic relapsing disorder hypothesized to be produced by drug-induced plasticity that renders individuals vulnerable to craving-inducing stimuli such as re-exposure to the drug of abuse. Drug-induced plasticity that may result in the addiction phenotype includes increased excitatory signaling within corticostriatal pathways which correlates with craving in humans and is necessary for reinstatement in rodents. Reduced cystine-glutamate exchange by system xc-appears to contribute to heightened ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 27 publications
(42 reference statements)
7
120
0
3
Order By: Relevance
“…NMDA receptors play a well-established role in the form of synaptic plasticity thought to underlie learning and memory, making them important targets in the delineation of disease pathophysiology and treatment (Coyle, 2006;Myers et al, 2011). Recent research has demonstrated that inhibiting presynaptic glutamate inhibitory autoreceptors, and thus augmenting glutamatergic synaptic neurotransmission, reduced craving in cocaine-addicted patients (Amen et al, 2011). Preclinical work with the GMS partial agonist Dcycloserine demonstrates that the selective potentiation of NMDA receptor signaling may be an effective means of enhancing extinction of drug conditioning (Paolone et al, 2009;Thanos et al, 2009;Myers and Carlezon, 2010), in a manner similar to the extinction of conditioned fear in agoraphobic patients (Ressler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptors play a well-established role in the form of synaptic plasticity thought to underlie learning and memory, making them important targets in the delineation of disease pathophysiology and treatment (Coyle, 2006;Myers et al, 2011). Recent research has demonstrated that inhibiting presynaptic glutamate inhibitory autoreceptors, and thus augmenting glutamatergic synaptic neurotransmission, reduced craving in cocaine-addicted patients (Amen et al, 2011). Preclinical work with the GMS partial agonist Dcycloserine demonstrates that the selective potentiation of NMDA receptor signaling may be an effective means of enhancing extinction of drug conditioning (Paolone et al, 2009;Thanos et al, 2009;Myers and Carlezon, 2010), in a manner similar to the extinction of conditioned fear in agoraphobic patients (Ressler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other regimens, including ShA regimens that do not lead to CP-AMPAR accumulation, provide insight into strategies for decreasing addictive behavior under different conditions. The most striking example concerns the drug N-acetylcysteine, which reduces cocaine-related behaviors after non-contingent cocaine exposure and ShA cocaine self-administration and has shown promise in clinical trials (Mardikian et al, 2007;Amen et al, 2011;Olive et al, 2012).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…NAC did not decrease cocaine self-administration or acute cocaine-induced hyperactivity, while it decreased repeated cocaine-induced escalation of drug intake and behavioural sensitization (Madayag et al, 2007). In addition, repeated NAC treatments also attenuated cocaineinduced increases in drug seeking in rats (Baker et al, 2003;Amen et al, 2010). Interestingly, NAC is also a prodrug for the synthesis of the endogenous antioxidant glutathione, and that NAC pretreatment protects animals from high dose methamphetamine-or amphetamineinduced DA neurotoxicity and behavioural changes by lowering oxidative stress levels (Fukami et al, 2004;Achat-Mendes et al, 2007).…”
Section: N-acetylcysteinementioning
confidence: 99%
“…In double-blind, placebocontrolled clinic trials, NAC was well tolerated and produced a significant reduction in cocaine-related withdrawal symptoms and/or cravings triggered by exposure to cocainerelated cues or by an experimenter-delivered intravenous injection of cocaine (LaRowe et al, 2006Amen et al, 2010 Table 3. Glutamate-based drug candidates in clinical trials Fig.…”
Section: N-acetylcysteinementioning
confidence: 99%